Profiling the participants in creative tourism activities: Case studies from small and medium sized cities and rural areas from Continental Portugal - Remoaldo, Paula (2022)
Although cultural tourists increasingly seek to experience cultural events actively and to directly engage in creative activities, empirical knowledge about the creative tourist remains limited. This study aims to characterize the motivations and profile of creative tourists. The data was collected through a survey of participants in creative tourism activities in Portugal developed by 40 pilot institutions of the CREATOUR project during 2017 and 2018, with 814 usable questionnaires collected and validated. The questionnaire had 30 questions and marked the first time this kind of research was conducted in Portugal. The questionnaire included questions on: the composition of their travel companions, their previous participation in a creative tourism experience, reasons for visiting the destination, their characterization of the creative tourism experience, an evaluation of their creative tourism experience, and their socio-demographic profile. Using a cluster analysis to analyse the data, three clusters were found: Novelty-Seekers, Knowledge and Skills Learners, and Leisure Creative-Seekers